2016
DOI: 10.1148/radiol.2016150409
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Expertise in Radiology: In Chest Radiograph Interpretation, “Expert” Search Pattern May Predate “Expert” Levels of Diagnostic Accuracy for Pneumothorax Identification

Abstract: Purpose To investigate the development of chest radiograph interpretation skill through medical training by measuring both diagnostic accuracy and eye movements during visual search. Materials and Methods An institutional exemption from full ethical review was granted for the study. Five consultant radiologists were deemed the reference expert group, and four radiology registrars, five senior house officers (SHOs), and six interns formed four clinician groups. Participants were shown 30 chest radiographs, 14 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 33 publications
3
59
0
4
Order By: Relevance
“…82 Experts in non-endoscopic studies have demonstrated fewer fixations required compared to non-experts to cover a region of interest. 83 Visual gaze patterns (VGPs), in particular gaze time per area of interest, significantly correlates with the colonic area examined with greater overlap in gaze position per area of interest and the determined area of colonic surface. 84 Heat patterns and gaze plots generated using LCI provide an objective marker of colonic mucosa visualised 85 (Fig.…”
Section: Eye-trackingmentioning
confidence: 99%
“…82 Experts in non-endoscopic studies have demonstrated fewer fixations required compared to non-experts to cover a region of interest. 83 Visual gaze patterns (VGPs), in particular gaze time per area of interest, significantly correlates with the colonic area examined with greater overlap in gaze position per area of interest and the determined area of colonic surface. 84 Heat patterns and gaze plots generated using LCI provide an objective marker of colonic mucosa visualised 85 (Fig.…”
Section: Eye-trackingmentioning
confidence: 99%
“…However, the in-depth detail that is provided by the eye gaze metrics reflects the significant differences in how visual tasks are performed between physicians of different experience. Kelly et al 10 reported similar findings, with registrars in their study having similar eye-tracking behaviour as consultants but lower levels of diagnostic accuracy, suggesting interpretation skills may predate expert diagnostic skills. With further investigation into these metrics and the role they have as markers of efficiency, they could be used as a tool to assess trainees transitioning into consultant roles.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, the domain-general temporal aspects of radiologists' performance were examined using eye-tracking [33,35], and by recording the reaction time [29,30] and trial completion time [34]. However, no differences were reported for gaze fixation characteristics [35], and radiologists demonstrated considerably faster reactions than other participants when detecting slight changes in non-radiological images [29] and finding low contrast targets [28,30], which allowed us to assume that the physical properties of stimuli might play a critical role in the temporal evaluation of performance depending on radiologist experience. In our study, we saw a tendency for students to consume more time compared to radiologists and residents when target-distractor similarity was high, however, no significance was reached.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive training leads to the increased tuning of visual perception [28] and changes in search strategy which radiologists implement during image reading [29]. Most previous studies have demonstrated the strong top-down influence of expertise when comparing the performance of radiologists and non-radiologists viewing medical images [29][30][31][32][33].…”
Section: Ergonomic Evaluation Of Visualization Methodsmentioning
confidence: 99%